Quality System Implementation By Selected Local Vendors In The Malaysian Automotive Industry - Patpanavan @ Pathmanathan, Shamini (2008)
Looking at the number of complaints on local cars by public has triggered the possibility of whether suppliers to car manufacturers could be the reason of numerous quality defects on local cars. As quality of product is also determined by the correct quality practice in an organization, the effectiveness of quality systems implementation, ISO 9000, QS 9000 or TS 16949, among local vendors becomes a factor in determining the quality of local cars. It is therefore, a need to address this issue emerges as Malaysia needs to compete aggressively in the automotive market to gain more sales, recognition and respect. The root of the quality problems has to be identified and either treated or eliminated. The study has only one objective, that is, to study the performance of vendors implementing quality systems. The research is a case study on selected local automotive vendors. Eight vendors and four car manufacturers were selected for the purpose of analysis. The study consists of both quantitative and qualitative methods. Questionnaires were sent via e-mail or hand to participants and are followed by a personal interview or via telephone conversation once the questionnaire is completed. Additional questions were asked during personal interview to gain more insight on relevant matters. The results were analyzed using the SPSS Software. The analysis showed that the performance of local cars depends on three parties; the suppliers who manufacture the car components, certification bodies who certify the suppliers and car manufacturers who assemble the cars. The main important issue in assuring quality in an organization is found not due to quality system but the management’s commitment to the quality system. Organizations that were studied on practice quality system but the quality practices were not fully implemented. Employers and employees alike do not understand the importance of quality in both work practice and produced parts. Other factors contributing to low quality production of cars includes car manufacturers’ leniency towards vendors, low technical know how and technology, attitude, lack of choice in selecting vendors and lack of testing facilities. There is slight difference in quality system implementation between companies that do not perform well and companies that perform well. This is because an organization’s performance depends on many other factors too; new part development, man power turnover and lack of technical expertise. There is difference in supplier expectations between local and foreign car manufacturers. It was also found that effective quality system implementation goes hand in hand with the quality of product produced.